ETIKA PROFESI HUKUM NOTARIS DITINJAU DARI PEMIKIRAN TIGA NILAI DASAR HUKUM GUSTAV RADBRUCH - Muhammad Nur Fikri Abdillah; Salma Nur Rochmah Setya Wardah; Indah Nur Cahyani (JURNAL ILMIAH NUSANTARA, 2024)
In the professional world, there are regulations that must be obeyed and ethics that must be followed. Notaries, as a legal profession, are no exception to the importance of complying with ethics in carrying out their duties. This article discusses the ethics of the notary profession by referring to Gustav Radbruch's thoughts on three basic legal values: justice, legal certainty and benefit to society. Previously, the meaning of the three basic legal values ​​according to Radbruch was presented. This research uses the library research method, collecting literature in the form of books, notes and reports of previous research results. Notaries, as public officials who have the authority to make authentic deeds, are expected to carry out their duties with integrity, fairness and professionalism. The Notary Code of Ethics is a reference in the legal profession. Notary personality ethics include fairness, moral integrity, and honesty towards all parties. The ethics of carrying out notary duties emphasizes professionalism, expertise and extensive experience. Meanwhile, notary service ethics requires considering the social benefits and social impacts of their actions. Gustav Radbruch's thoughts provide a framework for understanding and applying ethics in the notary profession. Justice refers to a fair attitude towards all parties. Legal certainty emphasizes clear and accurate documentation, as well as providing appropriate legal advice. Social utility emphasizes considering the positive impact on society as a whole. By implementing these basic values, notaries can carry out their duties with integrity and professionalism, and contribute to justice and legal certainty in society. Notary service ethics are an important basis for maintaining public trust and carrying out the profession well.